El cine del surandino peruano sobre el conflicto armado: género cinematográfico e hibridez desde los márgenes del establishment de Lima - Torres Vitolas, Miguel Ángel (2022)
This article proposes a critical regard on genre confronting this notion with Peruvian South Andean Cinema on the Armed conflict. We start by questioning genre notion, understood as a necessary condition in communicational practice between producers and audience. We are more interested in understanding how this notion points to a symbolic dispute from and among multiple agents involved in the cinematographic phenomenon. Then, we identify a characteristic that differences this cinema from hegemonic limeño cinema on armed conflict: genre hybridity. We found there a symbolic operation through which this cinema differs from Lima’s cinema and build its own identities.